Analisis Pengetahuan Kader dengan Penatalaksanaan SDIDTK di Posyandu Kelurahan Banjar Sari Kota Serang Provinsi Banten Tahun 2022 - Masluroh Masluroh; Risa Septiawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Based on a survey at Posyandu in Banjarsari Subdistrict, Serang City, from 18 posyandu, there were 10 posyandu in which one of the cadre members had received SDIDTK training. Each posyandu has 5 cadres. At the time of the preliminary study, there were 2 posyandu that had not implemented SDIDTK 100%, namely 10 cadres (20%) of the cadres in the 10 posyandu. The purpose of this study was to find out the knowledge analysis of cadres by implementing SDIDTK at Posyandu, Banjarsari Subdistrict, Serang City, Banten Province in 2022. Research methodology uses an analytical method with a cross sectional approach. The population in this study were all posyandu cadres in Banjarsari Village, Serang City in 2022, namely 50 posyandu cadres. The sample used was 50 posyandu cadres using quota sampling that met the inclusion and exclusion criteria. The results of this study indicate that there is a significant influence between the knowledge of cadres and the implementation of SDIDTK at Posyandu Kelurahan Banjarsari, Serang City, Banten Province in 2022 with a p-value of 0.001 and an OR value of 11,571. There is a significant influence between knowledge of cadres and the implementation of SDIDTK at Posyandu Kelurahan Banjarsari, Serang City Banten Province in 2022. It is hoped that cadres can increase cadre knowledge about SDIDTK through training or refreshments so that cadres are at the forefront of public health efforts and are able to become extensions of health workers in carrying out stimulation, early detection and early intervention on child development